Reductionist Pathways for Parasitism in Euglenozoans? Expanded Datasets Provide New Insights. Issue 2 (February 2021) - Butenko, Anzhelika; Hammond, Michael; Field, Mark C.; Ginger, Michael L.; Yurchenko, Vyacheslav; Lukeš, Julius
Abstract : The unicellular trypanosomatids belong to the phylum Euglenozoa and all known species are obligate parasites. Distinct lineages infect plants, invertebrates, and vertebrates, including humans. Genome data for marine diplonemids, together with freshwater euglenids and free-living kinetoplastids, the closest known nonparasitic relatives to trypanosomatids, recently became available. Robust phylogenetic reconstructions across Euglenozoa are now possible and place the results of parasite-focused studies into an evolutionary context. Here we discuss recent advances in identifying the factors shaping the evolution of Euglenozoa, focusing on ancestral features generally considered parasite-specific. Remarkably, most of these predate the transition(s) to parasitism, suggesting that the presence of certain preconditions makes a significant lifestyle change more likely. Highlights: Genome streamlining and the loss of certain metabolic pathways predate switches to parasitism in the evolution of Euglenozoa and are the result of a multistep process. Numerous features previously considered trypanosomatid-specific are present also in the free-living euglenozoans. They include nutrient-triggered attachment to surfaces, polycistronic transcription, trans -splicing, trypanothione, the loss of glutathione reductase, genome compaction via almost complete loss of cis -spliced introns, presence and even diversification of surface proteins, subtilisins, and carboxypeptidases. Rapid sequence evolution in Euglenozoa is not linked to parasitism, as it also occurs in free-living relatives of kinetoplastids.